2008
DOI: 10.1002/ceat.200700468
|View full text |Cite
|
Sign up to set email alerts
|

Process Control of an Alternating Aerobic‐Anoxic Sequencing Batch Reactor for Nitrogen Removal via Nitrite

Abstract: Nitrogen removal via nitrite is a novel technology and is becoming popular for engineering applications since it results in a saving of the aeration energy required for nitritation and external carbon sources for denitritation. An alternating aerobic-anoxic (AAA) operational pattern was applied in a sequencing batch reactor (SBR) process to improve the nitrogen removal efficiency and achieve partial nitrification via nitrite from industrial wastewater with influent alkalinity deficiencies. The results showed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Using partial nitrification followed by ANAMMOX for BNR saves 25% of the aeration cost in nitrification and does not require the addition of external organic carbon in the denitrification step. Efficient partial nitrification has been observed in intermittently aerated sequencing batch reactors (IASBRs) treating wastewater [13,14]. It is reported that IASBRs treating slaughterhouse wastewater achieved a NO 2 --N level of up to 96% of the total oxidized nitrogen (TON, NO 2 --N and NO 3 --N), in addition to COD and total nitrogen (TN) removals from wastewater of more than 94 and 92%, respectively [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Using partial nitrification followed by ANAMMOX for BNR saves 25% of the aeration cost in nitrification and does not require the addition of external organic carbon in the denitrification step. Efficient partial nitrification has been observed in intermittently aerated sequencing batch reactors (IASBRs) treating wastewater [13,14]. It is reported that IASBRs treating slaughterhouse wastewater achieved a NO 2 --N level of up to 96% of the total oxidized nitrogen (TON, NO 2 --N and NO 3 --N), in addition to COD and total nitrogen (TN) removals from wastewater of more than 94 and 92%, respectively [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Although two-step nitrification has been modeled previously , , the model for shortcut nitrification−denitrification kinetics has not been reported. Sequencing batch reactor (SBR) has been widely used in wastewater treatment not only for organic removal but also for nutrient removal including nitrogen and phosphorus ,, . SBR system is especially effective for biological nitrogen removal.…”
Section: Introductionmentioning
confidence: 99%
“…High temperature of 28 -38 °C was favorable for nitrogen removal via nitrite due to the fact that the specific growth rate of AOB was higher than NOB [51]. Nitritation can be maintained at room or low temperature and nitratation start-up can be promoted and accelerated at high temperature [52]. In temperature 10 -20 °C resulted a very low nitrite accumulation due to high specific growth rate of NOB than AOB [53].…”
Section: Temperaturementioning
confidence: 99%